2011
DOI: 10.4103/1119-3077.79270
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial glucose response to selected tropical fruits in normal glucose-tolerant Nigerians

Abstract: Banana, pawpaw, and pineapple produced a similar postprandial glucose response. Measured portions of these fruits may be used as fruit exchanges with pineapple having the most favorable glycemic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…This was done to eliminate inter-subject variability, which is a common confounder identified from previous research work. 20,21 The essence of ensuring the bean meals were administered on a weekly basis was to prevent second-meal effect on the glycaemic responses. 22,23 The bean meals were devoid of added ingredients in order to prevent the effect of unwanted extra carbohydrate from altering the Table 3: Glycaemic response of study participants.…”
Section: Discussionmentioning
confidence: 99%
“…This was done to eliminate inter-subject variability, which is a common confounder identified from previous research work. 20,21 The essence of ensuring the bean meals were administered on a weekly basis was to prevent second-meal effect on the glycaemic responses. 22,23 The bean meals were devoid of added ingredients in order to prevent the effect of unwanted extra carbohydrate from altering the Table 3: Glycaemic response of study participants.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, pineapple had a high GI and papaya had an intermediary GI, whereas watermelon and durian fruit were foods with a low GI. The AUC mean values in mmol.L -1 .min -1 of pineapple (62.6±10.5) and papaya (63.9±14.1) were almost identical among healthy subjects in another study; however, papaya GI (86±26.8) was high, while the one of pineapple (64.5±11.3) was moderate (23). Among the subjects with diabetes, AUC mean values expressed in mmol.L -1 .min -1 appeared as follows: pineapple (115.3±33.2), mango (101.6±28.7), and papaya (124.1±46.1); there was no significant difference between the GIs of those fruits; and the tested fruits had low GIs (24).…”
Section: Discussionmentioning
confidence: 87%
“…A study conducted in Malaysia on the GI of durian fruit, papaya, pineapple, and watermelon has shown an increase in blood glucose level over time, reaching its peak 30 minutes after the consumption of each of the four fruits, and then gradually declining till T120 minutes (22). On the contrary, a Nigerian study on ten healthy subjects has indicated that pineapple consumption causes a glycemic peak at T60 minutes, whereas papaya's glycemic peak comes earlier in T45 minutes (23). Among subjects with type 2 diabetes, pineapple peaks in 30 minutes, while banana, orange, mango and papaya peak in 60 minutes, after ingestion by measuring blood glucose levels every 30 minutes over a period of two hours (24).…”
Section: Discussionmentioning
confidence: 99%
“…The GIs of these tropical fresh fruits varied from 86% for pawpaw to 72% for watermelon, 62% for banana, 40% for orange, and 39% for apple. [1415] Hence, these results indicate the need to wash hand thoroughly with tap water and drying them after peeling or handling fruits. This should be recommended to patients and HCPs to ensure accurate monitoring of BG levels when using blood samples obtained by pricking the fingertip.…”
Section: Discussionmentioning
confidence: 99%